HUBUNGAN FAKTOR-FAKTOR USIA IBU, PARITAS, UMUR KEHAMILAN, DAN OVER DISTENSI DENGAN KEJADIAN KETUBAN PECAH DINI DI RUMAH SAKIT YOGYAKARTA - Rahayu, Budi (MEDIA ILMU KESEHATAN, 2018)
Background: Premature rupture of membranes (PROM)is a rupture of membranes before any signs of labor and awaited before the labor occurs. The problem of PROM is a major obstetric issue, because the impact of PROM is an infection in the maternal and ends in an increased incidence of cesarean section due to a failed normal childbirth and neonatal. Factors that causePROMitself is not known for certain, but if we know earlier about the predisposing factors of PROM preventive efforts will be more helpful and reduce maternal and neonatal morbidity and mortality. Objective: Relationship of maternal age, parity, gestational age, and over distention with incidence of premature rupture of membranes in Yogyakarta Hospital. Research Of Method: This research uses retrospective study approach with data focus case control approach. The case population in this research is all maternal mothers who experience premature rupture of membranes in RSUD Yogyakarta in 2017 obtained from medical record. Sampling technique is by total sampling with the number of 427 respondents. Data analysis used is bivariate analysis. Result: Parity has nothing to do with the incidence of premature rupture of membranes due to the value of p value 0.142> 0.05, with the OR value of 0.814. Age of pregnant women has nothing to do with the incidence of premature rupture of membranes because the value of p value 0.671> 0.05, with the value of OR 1.062. Age pregnancy has nothing to do with the incidence of premature rupture of membranes because the value of p value 0.288> 0.05, with OR 1,207 nialai. Uterine overdistesi has nothing to do with the incidence of premature rupture of membranes due to the p value of 0.571> 0.05, with the value of OR 1.240. Conclusion: There is no relationship between maternal age, parity, gestational age, and overdistence with premature rupture of membranes in Yogyakarta Hospital. Keywords: Maternal age, Parity, Age of Pregnancy, Overdistence, and premature rupture of membranes (PROM)